PENGARUH PENERAPAN APLIKASI SIA, DIGITAL MARKETING & E-COMMERCE TERHADAP PERTUMBUHAN LABA PADA UMKM KOTA BANDAR LAMPUNG - Febriyani, Aldo Anggit; Dharma, Fitra (AKUNTANSI DEWANTARA, 2024)
This study aims to analyze the impact of implementing accounting information system applications, e-commerce, and digital marketing on profit growth in SMEs in Bandar Lampung. It employs a quantitative approach, sampling all SMEs in the city through purposive sampling, resulting in 142 collected data. Data were obtained through questionnaires and interviews, analyzed using descriptive analysis, validity and reliability tests, classic assumption tests, and multiple linear regression analysis. The results show a positive influence of accounting information system applications on profit growth, as well as positive effects of e-commerce and digital marketing on profit growth for SMEs. The theory and implications highlight the positive influence of information technology on profit growth, stressing the importance for SMEs to enhance skills and knowledge in technology application for competitiveness and market expansion. The study's novelty lies in observing the positive impact of information technology application on profit growth in Bandar Lampung's SMEs, emphasizing a paradigm shift towards greater efficiency and effectiveness through modern information technology utilization